Islamic Economic Thought in Indian Subcontinent: Perceptions and Major Writings - Wani, Athar Shahbaz; Malik, Mohd Iqbal (Journal of Islamic Economics Literatures, 2025)
The decolonization of the Muslim world, pan-Islamic thought, and debates surrounding the Riba centric economy especially after the 1940s all contributed to the development of Islamic economics in the first half of 20th century. Islamic economics with its firm bases in the Quran, has gradually emerged in the 20th century as a result of Muslim intellectuals to reform their socio-political and economic structures. In the subcontinent the prominent efforts were made by Seoharvi (1938), Siddiqi (1943), Hamidullah (1936, 1941, and 1944), Gilani (1947), Yusufuddin (1950), and others. They all have discussed, evaluated and debated the Islamic economic thought and made its comparative analysis. This initial literary phase roughly from 1930-1970 has been earmarked with pervasive writings on major themes of Islamic Economics and its competence focused mostly on the concept of riba (usury) its material and spiritual shortcomings, flaws in the socialism and capitalist economic systems. Moreover, scholars from the sub-continent offered the earliest models of interest-free banking i.e. Uzair 1955, Nejatullah Siddiqui 1969, based on a two-tier Mudarabah, Profit Loss Sharing and Murabahah mechanism. In this context, the current study highlights the politico-economic factors that led to the development of Islamic Economics with a historical and revisionist perspective. The data presented in the research is updated and examines varied dimensions of Islamic Economic thought, together with making an illustration of the comprehensive writings on the subject.